PENYELESAIAN SENGKETA ALTERNATIF SEBAGAI SALAH SATU PILIHAN DALAM PENYELESAIAN SENGKETA DAGANG INTERNASIONAL - tengku dwi gita cahyani; m. hadyan yunhas purba (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2023)
ABSTRACTDisputes are a common thing to happen, so the settlement must also benefit both parties. Alternative dispute resolution or Alternative Dispute Resolution (ADR) is an option in solving the problems of the parties in the field of international trade. This settlement is carried out by means of choice of law and choice of jurisdiction which is stated in the contract clause. Prior to the arbitration stage, dispute resolution begins with negotiations first. However, the implementation of the execution is a bit difficult, because sometimes some parties do not want to carry out the award from the arbitration, so it is quite time-consuming and labor-intensive to return the matter to court. For this reason, when making contract clauses, there must be self-awareness to carry out decisions if a dispute does occur in international trade. As an example of alternative dispute resolution by Indonesia is regarding the Indonesia-Japan National Car Dispute, the point of the problem is where Japan feels that Indonesia is doing injustice to the automotive industry which at that time cut the cost of tax duties for national cars, even though Japan has a large target market in Indonesia. in the automotive case, this lawsuit was brought to International Arbitration and the lawsuit was won by Japan. Furthermore, it is explained how the procedure for resolving disputes and how alternative dispute resolution is an option in resolving international trade disputes. The research method in this journal uses a normative juridical qualitative method that conducts research on existing theories.Keywords: Disputes, International Trade, Arbitration